Beta-catenin accelerates human papilloma virus type-16 mediated cervical carcinogenesis in transgenic mice. - Gülay Bulut; Shannon Fallen; Elspeth M Beauchamp; Lauren E Drebing; Junfeng Sun; Deborah L Berry; Bhaskar Kallakury; Christopher P Crum; Jeffrey A Toretsky; Richard Schlegel; Aykut Üren (PLoS ONE, 2011)
Human papilloma virus (HPV) is the principal etiological agent of cervical cancer in women, and its DNA is present in virtually all of these tumors. However, exposure to the high-risk HPV types alone is insufficient for tumor development. Identifying specific collaborating factors that will lead to cervical cancer remains an unanswered question, especially because millions of women are exposed to HPV. Our earlier work using an in vitro model indicated that activation of the canonical Wnt pathway in HPV-positive epithelial cells was sufficient to induce anchorage independent growth. We therefore hypothesized that constitutive activation of this pathway might function as the "second hit." To address this possibility, we developed two double-transgenic (DT) mouse models, K14-E7/ΔN87βcat and K14-HPV16/ΔN87βcat that express either the proteins encoded by the E7 oncogene or the HPV16 early region along with constitutively active β-catenin, which was expressed by linking it to the keratin-14 (K14) promoter. We initiated tumor formation by treating all groups with estrogen for six months. Invasive cervical cancer was observed in 11% of the K14-ΔN87βcat mice, expressing activated β-catenin and in 50% of the animals expressing the HPV16 E7 oncogene. In double-transgenic mice, coexpression of β-catenin and HPV16 E7 induced invasive cervical cancer at about 7 months in 94% of the cases. We did not observe cervical cancer in any group unless the mice were treated with estrogen. In the second model, K14-HPV16 mice suffered cervical dysplasias, but this phenotype was not augmented in HPV16/ΔN87βcat mice. In summary, the phenotypes of the K14-E7/ΔN87βcat mice support the hypothesis that activation of the Wnt/β-catenin pathway in HPV-associated premalignant lesions plays a functional role in accelerating cervical carcinogenesis.